A clinical validation study for application of DBS in therapeutic drug monitoring of antidepressants. (March 2016) - Berm, Elizabeth JJ; Odigie, Blessing; Bijlsma, Maarten J; Wilffert, Bob; Touw, Daan J; Maring, Jan G
Background: A bridging study of plasma and DBS concentrations for therapeutic drug monitoring of antidepressants was performed.Results & methodology: Potassium-based hematocrit analysis was included. In addition, we defined acceptance criteria based on the differences between individual data points of plasma and DBS concentrations. These criteria were applied to test acceptability of error found in predicted nortriptyline plasma concentrations. Potassium-based hematocrit predicted a negative bias for DBS concentrations of amitriptyline, but not for the other compounds. To predict plasma concentrations of antidepressants based on DBS concentrations, a factor of 0.8, 0.65, 0.84 and 0.78 was found for nortriptyline, desmethylclomipramine, venlafaxine and desmethylvenlafaxine, respectively.Discussion & conclusion: Application of the factor and newly formulated acceptance criteria demonstrated prediction of nortriptyline plasma concentrations based on DBS concentrations.